2015
DOI: 10.7554/elife.07426
|View full text |Cite
|
Sign up to set email alerts
|

A functional link between the co-translational protein translocation pathway and the UPR

Abstract: Upon endoplasmic reticulum (ER) stress, the transmembrane endoribonuclease Ire1α performs mRNA cleavage reactions to increase the ER folding capacity. It is unclear how the low abundant Ire1α efficiently finds and cleaves the majority of mRNAs at the ER membrane. Here, we reveal that Ire1α forms a complex with the Sec61 translocon to cleave its mRNA substrates. We show that Ire1α's key substrate, XBP1u mRNA, is recruited to the Ire1α-Sec61 translocon complex through its nascent chain, which contains a pseudo-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
121
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(139 citation statements)
references
References 50 publications
16
121
1
1
Order By: Relevance
“…Collectively, we concluded that XBP1u mRNA is specifically recruited to the ER membrane by the SRP-mediated ERtargeting pathway. Our findings regarding SRP involvement in the ER-specific targeting of XBP1u are consistent with previous findings based on different approaches, although the role of translational pausing of XBP1u in the recognition of XBP1u by SRP was not previously evaluated (34).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Collectively, we concluded that XBP1u mRNA is specifically recruited to the ER membrane by the SRP-mediated ERtargeting pathway. Our findings regarding SRP involvement in the ER-specific targeting of XBP1u are consistent with previous findings based on different approaches, although the role of translational pausing of XBP1u in the recognition of XBP1u by SRP was not previously evaluated (34).…”
Section: Discussionsupporting
confidence: 82%
“…Because an N-terminal signal sequence causes cotranslational translocation of the protein into the luminal space of the ER, the mRNA should remain on the translocon, which indicates that the mRNA is able to be spliced on the translocon with high efficiency. This notion is consistent with a recently published paper showing that IRE1α directly associates with a translocon that could splice XBP1u mRNA (34).…”
Section: Discussionsupporting
confidence: 82%
“…Perhaps the most intriguing example of branch specificity was our observation that depletion of translocon subunits led to selective activation of the IRE1α branch, which is notable in light of recent studies suggesting that IRE1α, unlike ATF6 or PERK, acts in physical association with the translocon (Plumb et al, 2015). Given that we, in agreement with others (Shoulders et al, 2013), observed regulation of translocon expression to be uniquely under IRE1α control, this suggests a feedback model in which IRE1α monitors the state of translocation.…”
Section: Discussionmentioning
confidence: 58%
“…Three out of four subunits of the translocon-associated protein complex (TRAP) scored; and strikingly, among the 7 hits with the strongest phenotypes were all three genes that encode the ER protein-translocation channel or translocon ( SEC61A1 , SEC61B , SEC61G ) (Figures 4D, 4E, S4D). The phenotypes of SRP-targeting factors and the translocon were surprising because recent reports have shown that SRP-mediated recruitment of unspliced XBP1 (XBP1u) to the ER and IRE1α binding to the translocon are required for maximal XBP1 splicing in response to exogenous stress (Kanda et al, 2016; Plumb et al, 2015). Satisfyingly, targeting of both ERN1 (IRE1α) and XBP1 decreased reporter signal in the screen (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…Regulated IRE1-dependent decay of mRNA, a key component of the unfolded protein response, results in degradation of viral mRNA transcripts and spliced Xbp1 (13,35). However, there are multiple lines of evidence suggesting that IRF3 activation can result from other forms of noninfectious cell damage that involve Xbp1 splicing (17,18,36).…”
Section: Discussionmentioning
confidence: 97%